2018
DOI: 10.1016/j.neuroimage.2018.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Modeling white matter microstructure with fiber ball imaging

Abstract: Fiber ball imaging (FBI) provides a means of calculating the fiber orientation density function (fODF) in white matter from diffusion MRI (dMRI) data obtained over a spherical shell with a b-value of about 4000 s/mm or higher. By supplementing this FBI-derived fODF with dMRI data acquired for two lower b-value shells, it is shown that several microstructural parameters may be estimated, including the axonal water fraction (AWF) and the intrinsic intra-axonal diffusivity. This fiber ball white matter (FBWM) mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 47 publications
(95 citation statements)
references
References 49 publications
13
82
0
Order By: Relevance
“…to monopolar data with b‐values of 0 s/mm 2 and 6000 s/mm 2 and TE ranging from 90 ms to 150 ms. The assumed values for D a were 1.0, 1.5, 2.0, and 2.5 µm 2 /ms, which are representative of estimates obtained from microstructural modeling …”
Section: Methodsmentioning
confidence: 85%
“…to monopolar data with b‐values of 0 s/mm 2 and 6000 s/mm 2 and TE ranging from 90 ms to 150 ms. The assumed values for D a were 1.0, 1.5, 2.0, and 2.5 µm 2 /ms, which are representative of estimates obtained from microstructural modeling …”
Section: Methodsmentioning
confidence: 85%
“…The direction‐averaged TDE data (i.e., S¯2) are utilized in Equation , along with direction‐averaged data acquired with identical imaging parameters other than b being set to 0 (i.e., S¯1), to estimate the intra‐axonal diffusivity. An advantage of our method, in contrast to alternative SDE techniques, is the simplicity with which the intra‐axonal diffusivity is obtained. In fact, with the TDE approach, D a is the easiest parameter to determine rather than, as other studies have found, one of the most difficult .…”
Section: Discussionmentioning
confidence: 99%
“…To find the intra‐axonal diffusion tensor, D a , we use the fact that a standard FBI analysis of the same multidirection data obtained using the TDE sequence with b=0 is sufficient to estimate D a / D a . Given that D a is known, the full D a follows immediately.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations